MULTIPARADIGM APPROACH FOR IMMIGRATION RESEARCHS - Bobby Briando; Agung Sulistyo Purnomo; Sri Kuncoro Bawono (Jurnal Ilmiah Kajian Keimigrasian, 2019)
This article discusses a research paradigm from several perspectives which is so-called Multiparadigm. Multiparadigm encompasses Positivism; Criticism; Posmodernism; and the Spiritualism. This research is qualitatively descriptive by using explanative method. The result shows that acquiring the whole paradigm will lead to a contemplation that “truth” is not single, on the contrary it is quite diverse. In this sense, the truth in the context of human consciousness is a “realtive”measure. Nevertheless, the “Absolute” truth belongs only to the Source of Knowledge, the Lord of the Universe. A research in which using multiparadigm would widen the horizon in critical thingking. It is expected that point of view will be able to lead us to a revolutionary way of thingking and enhacing intellectual, emotional and spiritual awareness within researchers.